Uma intervenção psicoeducativa com cuidadores de idosos com demência - Dornelles, Andréia Rosana Andrade (2010)
The ageing of the Brazilian population comes accompanied by a growing number of cases of dementia, especially cases involving Alzheimer‟s disease, as the incidence of neurodegenerative diseases is directly related to age. Given that the majority of the Brazilian elderly are community-dwelling, but that there are few services for elderly people with dementia or for their caregivers, these families must discover, with or without adequate information, how to care for this person. This study focuses on the development and evaluation of an in-home intervention program, which aimed to improve the caregivers‟ capacity to act as therapeutic agents, increasing their abilities to maintain their own wellbeing and to promote the cognitive wellbeing of their relative with dementia, emphasizing the preparation of the caregivers to conduct cognitively stimulating activities. Five pairs of older people with dementia and their caregivers participated in this quasi-experimental study. To evaluate the impacts of the intervention program on the caregivers, data were collected before the beginning and after the conclusion of the program, using the following instruments: Zarit s Caregiver Burden Inventory, the Social Skills Inventory (Brazilian version), a qualitative evaluation of selected social skills, Lipp s Adult Stress Symptoms Inventory, knowledge acquisition tests (to evaluate the retention of new concepts at the end of each module), and a complementary questionnaire (to identify behaviors presented by the elderly relative that the caregiver considered to be problematic, how they managed these behaviors, and what they did to keep their relative active). Although cognitive stimulation can retard the progress of dementia, it cannot stop the advance of these diseases. A decrease in the elderly people‟s abilities during the intervention period would have a negative impact on indicators of the caregivers‟ wellbeing, interfering with the evaluation of the program. As such, the elderly people were also evaluated using the Mini Mental State Exam (MMSE) and the Pfeffer Examination for Functional Activities (PEFA). Results concerning the impacts of the intervention program for the caregivers indicated statistically significant differences for: (a) a reduction in stress levels, t(4) = 4.47, p = 0,011, (b) an improvement in the caregivers‟ average scores on the knowledge acquisition tests, t(4) = 23.91, p < 0,001, (c) a trend indicating improvement in the Social Skills Inventory scores (Brazilian version), t(4) = 2,36, p = 0,77, and (d) according to the results gained via the complementary questionnaire, a 57% improvement in the use of strategies to manage the elderly relative‟s problematic behaviors, as well as a 100% improvement in the caregivers‟ abilities to conduct cognitively stimulating activities with their elderly relative. However, the caregivers no longer engaged in these activities at the time of the follow-up evaluations. As such, the intervention program helped the caregivers acquire new knowledge as well as to improve their abilities to conduct cognitively stimulating activities and to manage stressful situations involving their elderly relative. However, we still need to identify supports that could help sustain the caregivers‟ use of cognitively stimulating activities with their elderly relative, following the conclusion of an intervention program like the one described in this study.